BENDING FATIGUE LIFE PREDICTION OF GEARS BASED ON DAMAGE SCALE FACTOR - GAO Xiang; YANG JianWei; LI Xin; WANG JinHai; LIU Fu (Jixie qiangdu)
To ensure the safe operation of mechanical transmission equipment, it is necessary to predict gears′ fatigue life accurately. Based on the cumulative damage theory and the flexural fatigue test results under two-stage loads, the relationship between the ratio of two-stage stress amplitudes and the bending fatigue damage is established in this paper. The relationship is used to improve the original model. The improved bending fatigue life prediction model can accurately predict the bending fatigue life of gears. Compared with the bending fatigue test results under multi-stage loading under various modes, the prediction result has a small deviation from the average test life.